MOLECULAR GENETIC CHARACTERISTICS OF MYCOBACTERIUM TUBERCULOSIS ISOLATES CIRCULATING IN ASTANA - Auganova, D.; Atavliyeva , S.; Amirgazin , A.; Akisheva , A.; Abeldenov , S.; Tsepke, A.; Tarlykov , P. (Eurasian Journal of Applied Biotechnology, 2024)
According to the World Health Organization, Kazakhstan takes a leading position in the number of cases of multidrug-resistant tuberculosis. This work is aimed at studying clinical isolates of Mycobacterium tuberculosis circulating in Astana in 2021–2022. Among 198 M. tuberculosis isolates collected, 175 (88.38%) belonged to the L2/Beijing family, and the remaining 23 samples (11.62%) belonged to the L4 family. During the research used genotyping aimed at determining the genetic family of M. tuberculosis, as well as whole-genome sequencing of selected 24 L2/Beijing isolates with their subsequent bioinformatics analysis. According to the analysis results, 62.5% of isolates were assigned to the Central Asia Outbreak genotype. The remaining genotypes were represented by Central Asia (20.8%), B0/W148 (12.5%) and Clade A (4.2%). Besides that, phenotypic and genotypic characterization of the resistance of selected isolates to anti-tuberculosis drugs was carried out. One of the possible reasons for the spread of resistant forms of tuberculosis in the country is the predominance of the Central Asia Outbreak genetic cluster associated with MDR-TB.